HATE SPEECH IN ARABIC LANGUAGE: CASE STUDY IN INSTAGRAM COMMENTS - Muhammad Yunus Anis; Likha Sari Anggreni; Eva Farhah (Journal of Islamic, Social, Economics and Development, 2018)
Nowadays, many people can gain the information access from many sides, such as television, social media, and so on. They can express their opinions, agreement and disagreement, like and hate. Many people can gain many information and opinions from social media, in the other hand; social media also becomes the main source of hate speech. This speech had the contents of hate, and it makes social public worried and disturbed, because it against some public social’s attributes, such as: gender, religion, racialism, colour, national origin, sexual orientation, disability, or other traits. This research will investigate the constructions of hate speech in arabic newspaper. The variants of hate speech will be analysed from the units of language and also the background conditions that make some people using hate speech in the flow of discourse. The second objective of the research elaborated the dominant themes of hate speech in the arabic newspaper, especially in the instagram comments using the contents analysis based on halliday approach. The qualitative method in this research had divided into three main parts, they are: collecting the data, analysing the data, and reporting the data. The main data in this research is arabic newspaper on-line, especially in arabic comments which had been appeared in instagram (al-jazeera english-arabic). This research can be hypothesized into two basic problems to be solved, they are: (1) the variant of hate speech in arabic language based on the units of language, and (2) the dominant themes of hate speech in arabic language. This research will be the model beyond the variants hate speech in all languages. By elaborating the hate speech, the people can avoid massively the units of language containing the sense of hate in social media.